A. Operator Relations

A. Operator Relations

A. Operator Relations A.1 Theorem 1 Let A and B be two non-commuting operators, then [1] α2 exp(αA)B exp(−αA)=B + α [A, B]+ [A, [A, B]] + .... (A.1) 2! Proof. Let f1(α)=exp(αA)B exp(−αA) , (A.2) then, one can expand f1 in Taylor series about the origin. We first evaluate the derivatives − − f1(α)=exp(αA)(AB BA)exp( αA) , so f1(0) = [A, B] . (A.3) Similarly − − f1 (α)=exp(αA)(A [A, B] [A, B] A)exp( αA) , so that f1 (0) = [A, [A, B]] . (A.4) Now, we write the Taylor’s expansion α2 f (α)=f (0) + αf (0) + f (0) + ... (A.5) 1 1 1 2! 1 or α2 exp(αA)B exp(−αA)=B + α [A, B]+ [A, [A, B]] + .. (A.6) 2! A particular case is when [A, B]=c,wherec is a c-number, then exp(αA)B exp(−αA)=B + αc , (A.7) in which case exp(αA) acts as a displacement operator. 364 A. Operator Relations A.2 Theorem 2: The Baker–Campbell–Haussdorf Relation Let A and B be two non-commuting operators such that [A, [A, B]] = [B,[A, B]] = 0 , (A.8) then α2 exp [α(A + B)] = exp αA exp αB exp − [A, B] (A.9) 2 α2 =expαB exp αA exp [A, B] . 2 Proof. Define f2(α) ≡ exp αA exp αB . (A.10) Then df (α) 2 =[A +exp(αA)B exp −(αA)]f (α) (A.11) dα 2 =(A + B + α [A, B])f2(α) , where in the last step, we used (A.6). Also, from the definition of f2(α), we can write df (α) 2 =exp(αA)A exp αB +exp(αA)exp(αB)B (A.12) dα =expαA exp αB [exp(−αB)A exp αB + B] = f2(α)(A + B + α [A, B]) . By comparing (A.11) and (A.12), we can see that f2(α)commuteswith (A+B +α [A, B]), thus one can integrate as a c-number differential equation, getting α2 α2 f (α)=exp (A + B)α + [A, B] =expα(A+B)exp [A, B] , (A.13) 2 2 2 thus obtaining the desired result. Another application of the Theorem 1 is taking A = aa†, (A.14) B = a or a† . As [n, a]=−a (A.15) A.3 Theorem 3: Similarity Transformation 365 and the higher order commutators also give a with alternating signs, thus α2 exp(αn)a exp(−αn)=a − αa + a + ... =exp(−α)a. (A.16) 2 Similarly exp(αn)a† exp(−αn)=exp(α)a† . (A.17) A.3 Theorem 3: Similarity Transformation exp(αA)f(B)exp−(αA)=f(exp(αA)(B)exp−(αA)) . (A.18) Proof. We start with the following identity [exp(αA)(B)exp−(αA)]n =exp(αA)B exp(−αA)exp(αA)B exp(−αA)... =exp(αA)Bn exp(−αA) . Then, for any function f(B) that can be expanded in power series, the Theorem 3 follows. As an interesting application, let us calculate exp −αa† + α∗a f(a, a†)exp αa† − α∗a = f[exp −αa† + α∗a a exp αa† − α∗a , exp −αa† + α∗a a† exp αa† − α∗a ] = f(a + α, a† + α∗) . Also exp −αa† f(a, a†)exp αa† = f(a + α, a†) , (A.19) exp (α∗a) f(a, a†)exp(−α∗a)=f(a, a† + α∗) , (A.20) exp (αn) f(a, a†)exp(−αn)=f[a exp(−α),a† exp(α)] (A.21) Other properties: One can easily show that da†l a, a†l = la†l−1 = , (A.22) da† dal a†,al = −lal−1 = − . da A more general version of the above relations is for a function f(a, a) which may be expanded in power series of a and a† ∂f(a, a†) a, f(a, a†) = , (A.23) ∂a† ∂f(a, a†) a†,f(a, a†) = − . (A.24) ∂a 366 A. Operator Relations Reference 1. Louisell, W.H.: Quantum Statistical Properties of Radiation. John Wiley, New York (1973) B. The Method of Characteristics We have a first-order partial differential equation: [1] Pp+ Qq = R, (B.1) where P = P (x, y, z),Q= Q(x, y, z),R= R(x, y, z), and ∂z ∂z p ≡ ,q ≡ , (B.2) ∂x ∂y and we wish to find a solution of (B.1), of the form z = f(x, y) . (B.3) The general solution of (B.1) is F (u, v)=0, (B.4) where F is an arbitrary function, and u(x, y, z)=c1 , (B.5) v(x, y, z)=c2 , is a solution of the equations dx dy dz = = . (B.6) P Q R Proof. If (B.5) are solutions of (B.6), then the equations ∂u ∂u ∂u dx + dy + dz =0, (B.7) ∂x ∂y ∂z and dx dy dz = = , P Q R must be compatible; thus, we must have 368 B. The Method of Characteristics Pux + Quy + Ruz =0, (B.8) and similarly for v Pvx + Qvy + Rvz =0. (B.9) On the other hand, if x and y are independent variables and z = z(x,y), then from (B.5), we get ∂z u + u =0, (B.10) x z ∂x ∂z u + u =0, y z ∂y and substituting (B.10) into (B.8) we get ∂z ∂z ∂u −P − Q + R =0, ∂x ∂y ∂z and (B.1) is satisfied. The second part of the proof is to show that the general solution of (B.1) is F (u, v)=0. (B.11) From (B.11), one writes ∂F ∂F ∂u ∂u ∂z ∂F ∂v ∂v ∂z = + + + =0, (B.12) ∂x ∂u ∂x ∂z ∂x ∂v ∂x ∂z ∂x ∂F ∂F ∂u ∂u ∂z ∂F ∂v ∂v ∂z = + + + =0. (B.13) ∂y ∂u ∂y ∂z ∂y ∂v ∂y ∂z ∂y We finally notice that (B.13) is satisfied considering (B.10). Example. Find the general solution of the equation ∂z ∂z x2 + y2 =(x + y)z. (B.14) ∂x ∂y In this case P = x2 , (B.15) Q = y2 , R =(x + y)z, and we have to find the solution of dx dy dz = = . (B.16) x2 y2 (x + y)z Reference 369 Integrating, first dx dy = , x2 y2 we get −1 −1 x + y = c1 . (B.17) On the other hand, x2 − dx − dy ( 2 1)dy dy dz = y = = , x2 − y2 x2 − y2 y2 (x + y)z from where we get x − y = c = v. (B.18) z 2 Combining (B.17) and (B.18), we get xy = c = u, (B.19) z 1 so the general solution can be put as xy x − y F , =0, (B.20) z z or if we write (B.20) in the equivalent form u = g(v) , (B.21) then the solution is xy x − y = g . (B.22) z z Reference 1. Sneddon, I.: Elements of Partial Differential Equations. (Mc-Graw Hill, New York (1957) C. Proof In this Appendix, we show the equation ⎡ ⎤ ⎣ − − − 2⎦ 2 − − δ(t tj)δ(t tk) S R ρaa = pRδ(t t ) . (C.1) j= k For regular pumping, one can put tj = t0 + jτ, where τ is the constant time interval between the atoms and t0 some arbitrary time origin [1]. In this case, there are no pumping fluctuations, and therefore, there are no correlations between the products of delta functions, that is δ(t − tj)δ(t − tk)S = δ(t − tj)S δ(t − tk)S (C.2) j,k j k = R2 . Now, we split the l.h.s. of the above equation in two parts 2 δ(t − tj)δ(t − tk)S + δ(t − tj)δ(t − tk)S = R , (C.3) j=k j=k 2 δ(t − tj)δ(t − tk)S + Rδ(t − t )=R , j= k thus proving the relation ⎡ ⎤ ⎣ − − − 2⎦ 2 − − δ(t tj)δ(t tk) S R ρaa = pRδ(t t ) j= k for p =1. In the Poissonian case, tj is totally uncorrelated from tk(j = k),so 2 δ(t − tj)δ(t − tk)S = δ(t − tj)S δ(t − tk)S = R , (C.4) j= k j k which proves (C.1) for p =0. Notice that in the above result, we are missing an atom in the second summation, so the above result is approximate, the approximation being very good when R>>1. (The error is of the order of R compared to R2.) A more general proof is found in the reference [2]. 372 C. Proof References 1. An excellent discussion on this point, as well and on noise supression in quantum optical systems is found in: Davidovich, L.: Rev. Mod. Phys., 68, 127 (1996) 2. Benkert, C., Scully, M.O., Bergou, J., Davidovich, L., Hillery, M., Orszag, M.: Phys. Rev. A, 41, 2756 (1990) D. Stochastic Processes in a Nutshell D.1 Introduction Classical Mechanics gives a deterministic view of the dynamical variables of a system. This of course is true, when one is not in a chaotic regime. On the other hand, in many cases, the system under study is only de- scribed by the time evolution of probability distributions. To show these ideas with an example, we take a look at the random walk in one dimension, by now, a classical problem [3]. A person moves in a line, taking random steps forward or backward, with equal probability, at fixed time intervals τ. Calling the position xn = na, then the probability that it occupies the site xn at time t is P (xn | t) and obeys the equation 1 1 P (x | t + τ)= P (x − | t)+ P (x | t) .

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    47 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us